An Experience Sampling and Cross-Cultural Investigation of the Relation between Pleasant and Unpleasant Emotion - SCOLLON, Christie N. (Institutional Knowledge at Singapore Management University, 2005)
The present study examined whether the relation between pleasant and unpleasant emotion varies across cultures and level of analysis (i.e., within-person vs. between-person). A total of 386 participants included European Americans, Asian Americans, Japanese, Indian, and Hispanic students. Momentary mood was assessed up to 7 times daily for one week. At the between-persons level, pleasant and unpleasant mood were positively correlated among Asian Americans and Japanese, but were uncorrelated among the other groups. Factor correlations at the within-person level were strongly negative in all cultures, suggesting that pleasant and unpleasant feelings are rarely experienced at the same time. Implications for dialectical experiences are discussed.